Analisis Kegiatan Remedial untuk Siswa Kelas V-C Yang Mengalami Kesulitan Penjumlahan dan Pengurangan Pecahan Campuran Di SDN Rangkah I Surabaya - Djayanti Wiulan Sari; Nova Estu Harsiwi (Jurnal Pengembangan dan Evaluasi Pendidikan, 2024)
Students who experience difficulties in learning are the teacher's responsibility to overcome them, one action that can be taken is through providing remedial activities. This research aims to determine the steps, obstacles and solutions for implementing remedial activities by class V-C teachers for students who experience difficulties in adding and subtracting mixed fractions at SDN Rangkah I Surabaya. This research method uses a descriptive qualitative approach with data collection techniques through observation, interviews and documentation. The results of the research show that the steps taken by the teacher include analysis of the results of the diagnosis of student difficulties based on test scores that are below the KKTP 60. Next, the teacher carries out remedial activity planning by arranging the day, date, time, method, media and questions that will be used . After careful planning, the teacher carried out remedial activities for four students who were experiencing difficulties and then assessed the results of the students' work. However, the implementation of remedial activities faces obstacles, such as taking a long time, the physical condition of students who are not enthusiastic, and differences in the characteristics of students' comprehension abilities. To overcome this obstacle, teachers maximize activity time, encourage students, and provide individual explanations to students who do not understand. The results of this research emphasize the importance of careful planning and approaches tailored to the characteristics of each student in remedial activities. Thus, remedial activities can be an effective solution in helping students overcome learning difficulties and achieve better learning outcomes.